2013
DOI: 10.1105/tpc.113.113886
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Histone Methylase CAU1/PRMT5/SKB1 Acts as an Epigenetic Suppressor of the Calcium Signaling Gene CAS to Mediate Stomatal Closure in Response to Extracellular Calcium

Abstract: (J-M.G).Elevations in extracellular calcium ([Ca 2+ ] o ) are known to stimulate cytosolic calcium ([Ca 2+ ] cyt ) oscillations to close stomata. However, the underlying mechanisms regulating this process remain largely to be determined. Here, through the functional characterization of the calcium underaccumulation mutant cau1, we report that the epigenetic regulation of CAS, a putative Ca 2+ binding protein proposed to be an external Ca 2+ sensor, is involved in this process. cau1 mutant plants display incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 64 publications
(147 reference statements)
1
27
0
Order By: Relevance
“…ABA affects the CAU1–CAS interaction and interrupts the suppression of CAS. CAS plays an important role in evoking [Ca 2+ ] cyt by regulating inositol‐1,4,5‐trisphosphate (IP3) biosynthesis (Weinl et al , Fu et al ). Furthermore, CAS is related to optimal photosynthesis (Wang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…ABA affects the CAU1–CAS interaction and interrupts the suppression of CAS. CAS plays an important role in evoking [Ca 2+ ] cyt by regulating inositol‐1,4,5‐trisphosphate (IP3) biosynthesis (Weinl et al , Fu et al ). Furthermore, CAS is related to optimal photosynthesis (Wang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Two different types of PRMTs catalyze asymmetric di-methylation (ADMA) and symmetric di-methylation (SDMA) on the Arg residues, respectively [ 17 , 21 ]. The prmt5 mutant has decreased level of histone H4 Arg3-SDMA, leading to enhanced drought tolerance [ 22 ]. A pair of PROTEIN ARGININE METHYLTRANSFERASE4 (PRMT4) homologs, AtPRMT4a and AtPRMT4b, is required for the asymmetrical di-methylation of Arg-2, Arg-17, and Arg-26 in histone H3 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of Ca 2+ signaling is mediated by Ca 2+ ‐binding proteins (McCormack and Braam ). Additionally, Ca 2+ ‐binding proteins, calmodulin‐like proteins, calcineurin B‐like protein and calcineurin B‐like protein‐interacting kinases mediate plant responses to a variety of external stresses (Tripathi et al , Fu et al ). Previous studies have also concluded that the endogenous Ca 2+ signaling molecule also regulates C4‐PEPC activity under natural or drought conditions in transgenic rice containing the maize C4‐PEPC gene (Li et al , Chen et al , Ren et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell‐specific accumulation of maize PEPC is correlated with demethylation at a specific site located greater than 3 kb upstream of the gene (Langdale et al ). A previous report indicated that the A. thaliana histone methylase CAU1/PRMT5/SKB1 acts as an epigenetic suppressor of the CAS calcium signaling gene to mediate stomatal closure and drought tolerance in response to extracellular calcium (Fu et al ). Whether the methylation of the exogenous promoter of C4‐PEPC influences rice drought responses is unclear and requires further study.…”
Section: Introductionmentioning
confidence: 99%